Dynamic parameter identification of parallel robots starting from the measurement of joints position and forces. - Díaz Rodríguez, Miguel; Mata, Vicente; Farhat, Nidal; Provenzano, Sebastián (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> In this paper the dynamic parameter identification of parallel robots starting from the measurement of positions and forces in the actuators is addressed. Methods for obtaining the time derivatives from the measurement of the angular displacement are evaluated. The procedures used are: a) Local Fitting, b) Finite Fourier series and c) Central differences. The identification is carried out by means of a linear model, with respect to the inertial parameters, obtained from the Newton-Euler equations. Linear models are used for friction modelling in the robot joints. Finally the parameter identification is evaluated experimentally over a 3-RPS parallel robot.